Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd010976.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic regimens for management of intra-amniotic infection

Abstract: This review included 11 studies (having low to moderate risk of bias). The quality of the evidence was low to very low for most outcomes, as per the GRADE approach. Only one outcome (duration of hospital stay) was considered to provide moderate quality of evidence when antibiotics (short duration) were compared with antibiotics (long duration) during postpartum management of intra-amniotic infection. Our main reasons for downgrading the quality of evidence were limitations in study design or execution (risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Common treatment for chorioamnionitis includes ampicillin, gentamicin, and clindamycin. 66,67 A recent study, however, examined treatment with an antibiotic regimen of ceftriaxone, clarithromycin, and metro-nidazole, which the authors found reduced histologic chorioamnionitis and funisitis. 68 Therefore, further investigation is necessary to understand how antibiotics may or may not alter the placental membrane microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Common treatment for chorioamnionitis includes ampicillin, gentamicin, and clindamycin. 66,67 A recent study, however, examined treatment with an antibiotic regimen of ceftriaxone, clarithromycin, and metro-nidazole, which the authors found reduced histologic chorioamnionitis and funisitis. 68 Therefore, further investigation is necessary to understand how antibiotics may or may not alter the placental membrane microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…A cursory review of cocited articles that were highly cited by articles citing the key articles retrieved additional potentially relevant publications that were not cited by the review authors in three reviews: Chapman et al (2014), Marshall et al (2014), andParekh et al (2014). In the case of Chapman et al (2014), the proposed method retrieved Sperling, Ramamurthy, and Gibbs (1987) and Gilstrap et al (1988); in the case of Marshall et al (2014), the method retrieved Roten, Baker, and Gray (2013); and in the case of Parekh et al (2014), the method retrieved Littlejohn, Tarling, Flynn, Ordman, and Aiken (1996). Although these publications may have been retrieved and subsequently excluded by the authors of these reviews, it is also possible that they were not retrieved at all.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy rate per review also improves substantially, ranging from 70% in the case of Parekh et al (2014) to 100% in the cases of Jackson, Veeratterapillay, Harding, and Dorkin (2014), Liu et al (2014), Mackeen et al (2014), Maguire, Weston, Singh, and Marson (2014), McNab et al (2014), Rimmer et al (2014), and Song et al (2014). The method missed a single study in the cases of Day et al (2014), Flowers, Hartley, Todkill, Stranges, andRees (2014), Marshall, Gowing, Ali, andLe Foll (2014), andMcRobbie, Bullen, Hartmann-Boyce, andHajek (2014), two studies in the cases of Chapman, Reveiz, Illanes, and Bonfill Cosp (2014) and Tan et al (2014), and three studies in the case of Parekh et al (2014).…”
Section: Journal Of the Association For Information Science And Technmentioning
confidence: 97%
See 2 more Smart Citations